Metal–Ceramic Layered Materials and Composites Manufactured Using Powder Techniques1. Issue 10 (7th October 2014) - Slawik, Tim; Bergner, Anne; Puschmann, Roberto; Franke, Peter; Raethel, Jan; Behnisch, Thomas; Scholl, Roland; Berger, Lutz‐Michael; Moritz, Tassilo; Zelm, Roland; Gude, Maik; Michaelis, Alexander; et al.
<x xml:space="preserve">Abstract</x> The manufacturing of metal–ceramic composites was investigated as part of subproject "C3–CerMetComp" at the ECEMP Excellence Cluster in Dresden. Three different manufacturing technologies were investigated: (i) Thermal spraying for the preparation of metal–ceramic multilayers; (ii) tape casting of layered composites followed by a co‐sintering step (in order to prevent defects during co‐sintering the sintering behavior of the metallic material was adjusted to the shrinkage behavior of the ceramic); and (iii) hot pressing of zirconia‐metal fiber composites with homogenously distributed fibers and subsequent evaluation by means of fracture toughness testing.